Molecular mechanism of GIRK2 channel gating modulated by cholesteryl hemisuccinate - Cui, Meng; Lu, Yongcheng; Ma, Xinyi; Logothetis, Diomedes E. (Frontiers in Physiology, 2024)
Cholesterol, an essential lipid of cell membranes, regulates G protein-gated inwardly rectifying potassium (GIRK) channel activity. Previous studies have shown that cholesterol activates GIRK2 homotetrameric channels, which are expressed in dopaminergic neurons of the brain. Deletion of GIRK2 channels affects both GIRK2 homo-and heterotetrames and can lead to abnormal neuronal excitability, including conditions such as epilepsy and addiction. A 3.5 Å cryo-EM structure of GIRK2 in complex with CHS (cholesteryl hemisuccinate) and PIP2 (phosphatidylinositol 4,5-bisphosphate) has been solved. This structure provides the opportunity to study GIRK2 channel gating dynamics regulated by cholesterol using gating molecular dynamics (GMD) simulations.In the present study, we conducted microsecond-long GMD simulations on the GIRK2 channel in its APO, PIP2, and PIP2/CHS bound states, followed by systematic analysis to gain molecular insights into how CHS modulates GIRK2 channel gating. We found that CHS binding facilitates GIRK2 channel opening, with 43 K + ion permeation events observed, compared to 0 and 2 K + ion permeation events for GIRK2-APO and GIRK2/PIP2, respectively. Binding of CHS to the GIRK2 channel enhances PIP2 and channel interactions, which is consistent with previous experimental results. The negatively charged PIP2 alters the internal electrostatic potential field in the channel and lowers the negative free energy barrier for K + ion permeation.